The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1460-9592.2006.02031.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with dexmedetomidine for diagnostic and interventional cardiac catheterization in children

Abstract: This initial experience showed dexmedetomidine, with or without the addition of propofol, may be a suitable alternative for sedation in spontaneously breathing patients undergoing cardiac catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 10 publications
0
79
0
5
Order By: Relevance
“…Dexmedetomidine has been found to be useful in sedation during mechanical ventilation, prevention of emergence delirium, after general anaesthesia and procedural sedation during noninvasive radiological procedures [49]. Munro et al, [50] reported dexmedetomidine as the primary agent for sedation during cardiac catheterization in infants and children. Kristin et al, [51] suggested that invasive procedures can successfully be performed in spontaneously breathing infants and toddlers with congenital heart disease using dexmedetomidine 1-3 mcg/ kg alone or in addition to low dose ketamine.…”
Section: Paediatric Usementioning
confidence: 99%
“…Dexmedetomidine has been found to be useful in sedation during mechanical ventilation, prevention of emergence delirium, after general anaesthesia and procedural sedation during noninvasive radiological procedures [49]. Munro et al, [50] reported dexmedetomidine as the primary agent for sedation during cardiac catheterization in infants and children. Kristin et al, [51] suggested that invasive procedures can successfully be performed in spontaneously breathing infants and toddlers with congenital heart disease using dexmedetomidine 1-3 mcg/ kg alone or in addition to low dose ketamine.…”
Section: Paediatric Usementioning
confidence: 99%
“…Limited data on adult population undergoing dental procedural sedation with dexmedetomidine has shown it to efficacious and safe with sufficient analgesia, but limited amnesia and prolonged recovery time [47][48][49][50] . Although generally effective for sedation for noninvasive and short procedure, dexmedetomidine as sole agent has not been uniformly successful for invasive procedures [51][52][53][54][55] . It is slowly losing the popularity as sole agent for procedural sedation due to its slow onset, delayed recovery, minimal analgesia and limited amnesia.…”
Section: Benzodiazepines (Bzd)mentioning
confidence: 99%
“…It has been successfully used for diagnostic radiologic procedures, like MRI and CT scans, and for invasive procedures, like placement of central venous lines in infants, bronchoscopy and laryngoscopy, cardiac catheterization and others 59,60 . Dexmedetomidine has been also used to provide sedation in the postanesthesia care unit following sevoflurane anesthesia to decrease the incidence of agitation in the pediatric population, and to allow intubation in a sedated pediatric patient.…”
Section: Pediatric Procedural Sedationmentioning
confidence: 99%